Peran Konseling Dalam Proses Pembinaan Kepribadian Anak Binaan - Akmal Nur Fauzy; Ali Muhammad (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The Special Child Development Institute is not only a place for children who are serving criminal periods. However, children will be given coaching so that they can change into better humans and be useful for society in the future. The role of counseling in the Special Child Development Institute is very important and helps in providing personality development programs for children. Counseling will help with the problems your child faces and the needs he needs to change into a better human being. This research method uses content analysis of various journals or scientific papers related to problems in research. The purpose of this study is to find out the importance of the role of counseling in the process of coaching child prisoners. The punishment for a person who violates the law is the loss of independence. This is not easy to deal with, especially for children. The existence of counseling helps children to adapt to the new environment in prison and is able to provide encouragement to serve their criminal period. Counselors can be a bridge for children in expressing their problems by using a variety of good communication.